2019
DOI: 10.1161/strokeaha.118.023838
|View full text |Cite
|
Sign up to set email alerts
|

Association of Perforator Stroke After Basilar Artery Stenting With Negative Remodeling

Abstract: Background and Purpose— We try to evaluate whether plaque features and perforator stroke after intracranial stenting is associated with the arterial remodeling patterns in patients with severe basilar artery stenosis. Methods— We studied patients with symptomatic intracranial arterial stenosis who underwent high-resolution magnetic resonance imaging from September 2014 to January 2017. Among them, patients with basilar artery stenosis underwent angiopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Our study found one patient with overperfusion and one patient with hemorrhage in the early stenting group; no patient had overperfusion of intracranial hemorrhage in the later stenting group. Third, from our data we found that more lesions in the early group were in the intracranial vertebral and basilar artery, which has a higher risk of leading to perforator stroke than anterior circulation 19. With regard to our findings, we speculate that intracranial stenting on recently symptomatic, still vulnerable plaques are more likely to cause plaque dislodgement, perforator stroke, and intracranial hemorrhage.…”
Section: Discussionsupporting
confidence: 49%
“…Our study found one patient with overperfusion and one patient with hemorrhage in the early stenting group; no patient had overperfusion of intracranial hemorrhage in the later stenting group. Third, from our data we found that more lesions in the early group were in the intracranial vertebral and basilar artery, which has a higher risk of leading to perforator stroke than anterior circulation 19. With regard to our findings, we speculate that intracranial stenting on recently symptomatic, still vulnerable plaques are more likely to cause plaque dislodgement, perforator stroke, and intracranial hemorrhage.…”
Section: Discussionsupporting
confidence: 49%
“…Strong enhancement was equal to or stronger than that of the pituitary infundibulum (eFigure 4 in the online-only Data Supplement). 19 In this study, positive remodelling, diffuse distribution, intraplaque haemorrhage and strong enhancement were recognized as ICAP-vulnerable features as previous studies have showed their close relationships with future ischemic events. [14][15][16][17] Image reconstruction was performed at the workstation.…”
Section: Imaging Analysis and Measurementsmentioning
confidence: 71%
“…Strong enhancement was equal to or stronger than that of the pituitary infundibulum (eFigure 4 in the online-only Data Supplement). 19…”
Section: Methodsmentioning
confidence: 99%
“…We adopted the same principle when interpreting HRMRI imaging for arterial remodeling and vessel wall features as we published before with small intra-observer and inter-observer variability [10, 17, 21]. The intra- and inter-observer variability of the two HRMRI scanners and identified vessel wall features were good to excellent (weighted k = 0.82, 95% CI: 0.46, 1.00 and 0.83, 95% CI: 0.41–1.00, respectively).…”
Section: Methodsmentioning
confidence: 99%